Secondhand [compact disc, unabridged] : travels in the new global garage sale - Minter, Adam, 1970- (Dreamscape Media, LLC, 2020)
A global exploration of the hidden market for used stuff follows unwanted, obsolescent objects' journeys into a reusable future that transforms the way people live and work.